2020
DOI: 10.1111/acv.12616
|View full text |Cite
|
Sign up to set email alerts
|

Current landscape attributes and landscape stability in breeding grounds explain genetic differentiation in a long‐distance migratory bird

Abstract: Numerous studies have highlighted a major role of isolation by both geographic distance and current landscape resistance in controlling bird population genetic differentiation. However, the importance of past landscape features or landscape temporal stability in shaping population genetic structure remains undervalued, particularly in birds. We assessed the role of isolation by landscape resistance – derived from current landscape attributes and measures of landscape stability –, in comparison to geographic is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 98 publications
1
12
0
Order By: Relevance
“…García et al (2021) found evidence of IBR in a long‐distance migrant passerine bird, the bluethroat Luscinia svecica , when investigating more scattered populations over a wider area than in our study. The authors suggested that the known high philopatry of the investigated populations was probably involved in determining the observed restriction in gene flow (García et al, 2021). In fact, despite their high movement capability, dispersal of migratory birds can be restricted by high philopatry (e.g., Ceresa et al, 2016; Hansson et al, 2002), probably due to risks and costs connected to dispersal (e.g., increased mortality, physiological costs; Plissner & Gowaty, 1996; Waser et al, 1994).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…García et al (2021) found evidence of IBR in a long‐distance migrant passerine bird, the bluethroat Luscinia svecica , when investigating more scattered populations over a wider area than in our study. The authors suggested that the known high philopatry of the investigated populations was probably involved in determining the observed restriction in gene flow (García et al, 2021). In fact, despite their high movement capability, dispersal of migratory birds can be restricted by high philopatry (e.g., Ceresa et al, 2016; Hansson et al, 2002), probably due to risks and costs connected to dispersal (e.g., increased mortality, physiological costs; Plissner & Gowaty, 1996; Waser et al, 1994).…”
Section: Discussionsupporting
confidence: 43%
“…More generally, birds are underrepresented in landscape genetic studies, possibly due to a preconceived assumption of lack of landscape effects on dispersal in this taxon (Kozakiewicz et al, 2018). García et al (2021) found evidence of IBR in a long-distance migrant passerine bird, the bluethroat Luscinia svecica, when investigating more scattered populations over a wider area than in our study. The authors suggested that the known high philopatry of the investigated populations was probably involved in determining the observed restriction in gene flow (García et al, 2021).…”
Section: Discussionmentioning
confidence: 48%
“…This dataset was used to evaluate: (i) genetic differentiation on the basis of F ST values, as a measure of pairwise genetic distance; and, (ii) genetic structure by means of Rgeneland 4.0.4 (Guillot et al, 2005), a package that applies a Bayesian clustering method to infer a number of clusters (K) of individuals. The achieved four clusters (Figure 1) were already considered in a previous study (García et al, 2020) dealing with the genetic differentiation of the Iberian bluethroat. Further methodological information can also be found in Alda et al (2013).…”
Section: Genetic Divergence: Microsatellite Genotyping Genetic Struct...mentioning
confidence: 95%
“…The phenotypic (Arizaga et al, 2006;García et al, 2017;Hogner et al, 2013) and genotypic (Johnsen et al, 2006(Johnsen et al, , 2007 variation of this species constitutes a complex subspecific mosaic associated to differences in geographic morphs and life history, where the Iberian breeding bluethroat L. s. azuricollis is considered among the most ancestral forms (Johnsen et al, 2006). This subspecies is distributed across strong geographical and environmental gradients in northwestern Iberian mountains, where it shows a moderate degree of genetic differentiation (Alda et al, 2013;García et al, 2020). Iberian bluethroats breed along an altitudinal gradient ranging from 750 to 2400 m a.s.l., under considerably different climatic conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation